CLIMATE CHANGE, POLICIES AND ADAPTATION FOR A RESILIENT FUTURE IN AGRICULTURE - Afolabi, Ekundayo; Ismail, Olawale F.; Kagbu, Joyce Hauwa (FUDMA JOURNAL OF SCIENCES, 2025)
Biodiversity on planet Earth once existed in harmonious balance. However, agricultural technological advancements have significantly transformed farming practices. Though, these changes have increased efficiency, they have also triggered human activities to contribute to climate change impacts on the global community. These impacts pose significant threats to our planet and food security. Consequently, it is imperative to establish policies and adaptation strategies to address climate change challenges and ensure sustainable climate and food security. This article logically reviews relevant literature, focusing on critical issues and the implications of climate change. The objectives are to propose strategic policies that protect biodiversity, promote technological innovation, and robust adaptation plans to foster a resilient future. The negative impacts of climate change necessitate comprehensive and well-considered responses from nations, because proactive approaches to these challenges have been insufficient, especially in developing nations compared to their developed counterparts. This article therefore logical argues that the world, especially the developing nations urgently need to create effective policies, develop robust adaptation plans, implement practical measures to regulate human activities and excesses at national and local levels and mitigate their adverse effects. More so, they should develop strategic frameworks for managing both biodegradable and non-biodegradable waste. Additionally, Sub-Sahara Africa, where Nigeria belongs to must strategically establish ideological structures that identify the underlying causes of ongoing climate change and assess climate risks. These initiatives should not only provide solutions for a healthier ecosystem and generate revenue to build a resilient future that enhances livelihoods.
Keywords: Strategy; Policies; Mitigation; Adaptation; Resilient